KONSEP DAN GAGASAN PENGENALAN PENDIDIKAN ANTIKORUPSI BAGI ANAK DALAM RANGKA MEWUJUDKAN GENERASI YANG BEBAS KORUPSI - S, Laurensius Arliman (Universitas Islam Negeri Raden Fatah Palembang, 2017)
Corruption is a crime that damages the nation of Indonesia; imagine if allowed to breed corruption in Indonesia, the Indonesian nation forward would be destroyed. Children as the successor generation of people, should be given education of good quality, one that can be taught to children is the anti-corruption education. Through this anti -corruption education, the child will know that corruption is a very ugly action, and opposed by all of society. This paper describes the concept of anti-corruption education in schools, taught in formal education. The concept of this education must start from the family , school, community and the government and other institutions that against children. The idea that the authors offer is implementing anti -corruption education is from the start their education at the bottom until the end for the child, other than that the government should provide education for teachers against corruption, and provide facilities that support, among other things: books, internet access, simulated forms of corruption. Moreover invites the public and law enforcement agencies in combating corruption are mutually reinforcing.